2017
DOI: 10.1134/s0006297917090012
|View full text |Cite|
|
Sign up to set email alerts
|

How fucose of blood group glycotypes programs human gut microbiota

S. V. Kononova

Abstract: Formation of appropriate gut microbiota is essential for human health. The first two years of life is the critical period for this process. Selection of mutualistic microorganisms of the intestinal microbiota is controlled by the FUT2 and FUT3 genes that encode fucosyltransferases, enzymes responsible for the synthesis of fucosylated glycan structures of mucins and milk oligosaccharides. In this review, the mechanisms of the selection and maintenance of intestinal microorganisms that involve fucosylated oligos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 144 publications
0
6
0
Order By: Relevance
“…While sialic acids confer a negative charge to the glycoconjugate, terminal fucose residues confer hydrophobicity, but both are associated with mucosal protection and their alteration may result in disease ( 72 , 75 ). Thus, human fucosyltransferases and their expression have been studied for their importance in inflammation, mucosal colonization, and host immune response modulation ( 83 , 84 ), and more recently, their importance for the maintenance of healthy gut microbiota profiles has been stressed out ( 85 , 86 ). In R gills, a moderate increase in Fuc terminal residues was observed in the lamellar goblet cells and those of the epithelium covering the proximal cartilage, and fucosyltransferase expression appeared upregulated in fish with high infection intensity ( Figures 2 , 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…While sialic acids confer a negative charge to the glycoconjugate, terminal fucose residues confer hydrophobicity, but both are associated with mucosal protection and their alteration may result in disease ( 72 , 75 ). Thus, human fucosyltransferases and their expression have been studied for their importance in inflammation, mucosal colonization, and host immune response modulation ( 83 , 84 ), and more recently, their importance for the maintenance of healthy gut microbiota profiles has been stressed out ( 85 , 86 ). In R gills, a moderate increase in Fuc terminal residues was observed in the lamellar goblet cells and those of the epithelium covering the proximal cartilage, and fucosyltransferase expression appeared upregulated in fish with high infection intensity ( Figures 2 , 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Structural and functional studies are now starting to reveal insights into why individuals expressing different HBGAs are at an increased risk of infections such as those caused by Vibrio cholera , Pseudomonas aeruginosa , norovirus, rotavirus and Helicobacter pylori 17 , 28 . By developing Lewis antigen cell-based models of the human small intestine, as well as performing docking studies, we have further defined why HBGA Le a – expressing non-secretor ( FUT2 − / − ) individuals, or young children (<2 years of age) are more susceptible to ETEC expressing CFA/I, or other related CFs family members 5 , 6 , 8 , 28 . Subsequently, our understanding and characterisation of these host-pathogen binding patterns could represent a critical point at which the adherence of ETEC expressing CFA/I and related CF family members, can be prevented with vaccines and/or anti-infection therapeutics that block this interaction (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we have also observed that Bangladeshi children with the Le(a+ b−) phenotype are more likely to be infected by ETEC expressing the colonisation factor antigen I (CFA/I) and the related ETEC CF family fimbriae or pili 6 . The likely explanation for this being, CFA/I could bind to Le a glycolipid structures present in the small intestinal mucosal layer of very young children (<2 years of age) and individuals with FUT2 non-secretor status 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, the secretor status of the FUT2 gene was suggested as a close correlation with a variety of gastrointestinal diseases, including IBD (Tang et al, 2021 ), and diseases caused by viruses, mainly norovirus (Nov) (Lindesmith et al, 2003 ; Currier et al, 2015 ) and rotavirus (RV) (Galeev et al, 2021 ). In fact, the reason behind this phenotype determines the presence or absence of HBGA, which consists of an attachment site and a carbon source of intestinal microbiota (Tong et al, 2014 ; Kononova, 2017 ), and the major binding saccharide of some viruses, including NoV (Chen et al, 2011 ) and RV (Sharma et al, 2020 ). Recently, alteration of the composition and function of the gut microbiota, namely dysbiosis, which was suggested, may greatly contribute to the pathogenesis of IBD.…”
Section: The Biosynthesis Of Hbgamentioning
confidence: 99%